Improving the Quality of the Goods Delivery Supply Chain System with the Integration of Lean Six Sigma and AHP Methods - Muhammad Iqbal Maulana; Hana Catur Wahyuni (Procedia of Engineering and Life Science, 2021)
Astrans Putra Logistik Ltd. is a logistics service company with shipping routes in Sidoarjo, Denpasar, Lombok and NTB. Some of the problems that occur, such as delays in the pick-up process of goods to the load that large but not enough for departure, cause the quality of the supply chain system to be poor. So this research needs to be done with the aim of knowing the point of waste in the supply chain, identifying the sigma value, and determining the priority for its improvement. Quality improvement is carried out using the Lean Six Sigma method with AHP integration as a priority selection for improvement. From the research results, it was found that there was waste that caused 3 (three) CTQ, namely delivery was delayed, goods were damaged or leaked, and there was a difference in the number of goods. The company's DPMO value is 34272 with a sigma value of 3.34. The priority for improvements that can be made based on AHP weight, namely check the package packages before they are sent (0,353), make SOP for the preparation of goods (0,167), and apply SOP for goods checking documents (0,142).